An in vitro vascularized micro-tumor model of human colorectal cancer recapitulates in vivo responses to standard-of-care therapy. Issue 7 (19th February 2021) - Hachey, Stephanie J.; Movsesyan, Silva; Nguyen, Quy H.; Burton-Sojo, Giselle; Tankazyan, Ani; Wu, Jie; Hoang, Tuyen; Zhao, Da; Wang, Shuxiong; Hatch, Michaela M.; Celaya, Elizabeth; Gomez, Samantha; et al.
Abstract : VMTs recapitulate in vivo drug responses and also reconstitute the cellular diversity of tumors. Abstract : Around 95% of anti-cancer drugs that show promise during preclinical study fail to gain FDA-approval for clinical use. This failure of the preclinical pipeline highlights the need for improved, physiologically-relevant in vitro models that can better serve as reliable drug-screening and disease modeling tools. The vascularized micro-tumor (VMT) is a novel three-dimensional model system (tumor-on-a-chip) that recapitulates the complex human tumor microenvironment, including perfused vasculature, within a transparent microfluidic device, allowing real-time study of drug responses and tumor–stromal interactions. Here we have validated this microphysiological system (MPS) platform for the study of colorectal cancer (CRC), the second leading cause of cancer-related deaths, by showing that gene expression, tumor heterogeneity, and treatment responses in the VMT more closely model CRC tumor clinicopathology than current standard drug screening modalities, including 2-dimensional monolayer culture and 3-dimensional spheroids.